Legal Analysis of ‘Pump and Dump’ Schemes in Indonesia’s Capital Market: Perspectives and Prevention - Anggra, Philip; Lie, Gunardi (Jurnal Ilmiah Wahana Pendidikan, 2025)
The economic development and capital market growth have led to theemergence of many market manipulation issues in Indonesia andworldwide. Legal frameworks and challenges associated with addressing'pump and dump' schemes in the Indonesian capital market underscore theneed for strong legal strategies and regulatory oversight to protect investorsand maintain market integrity. The 'pump and dump' scheme, characterizedby artificially inflating stock prices followed by rapid selling, is asignificant form of market manipulation that undermines investorconfidence and market stability. While Indonesia has laws related tomarket manipulation, primarily found in the Capital Market Law (Law No.8/1995) and various regulations issued by the Financial Services Authority(OJK), they do not immediately solve all capital market issues inIndonesia. Operational challenges and limitations faced by regulatorybodies in detecting and prosecuting perpetrators, including technologydeficiencies, resource constraints, and the need for more effective interagencycooperation, are highlighted. It is emphasized that while currentlaws provide a framework for action, there are still loopholes that allowmanipulators to exploit the system. A multifaceted approach to preventionis proposed, suggesting enhancements in legal provisions, greaterregulatory cooperation, and broader use of technology in supervision andenforcement. This legal analysis aims to contribute to ongoing discussionsand assist policymakers and stakeholders in refining the regulatorymechanisms governing the Indonesian capital market.